Biologi Stenocranus pacificus Kirkaldy (Hemiptera: Delphacidae) pada tanaman jagung (Zea mays L.) di rumah kasa - Dosma Ulina Simbolon; Maryani Cyccu Tobing; Darma Bakti (Perhimpunan Entomologi Indonesia, 2020)
Stenocranus pacificus Kirkaldy (Hemiptera: Delphacidae) is destructive pest on corn plants in South Lampung and it has been reported to cause corn damages in North Sumatra. The objective of this research was to study some aspects biology of S. pacificus on corn plants in screenhouse. The research was conducted by observing the biology of S. pacificus that was reared on corn plants in screenhouse. The results showed that life cycle of S. pacificus was 38–47 (41,60 ± 3,19) days: egg was 9–11 (10,20 ± 0,79) days, the first instar nymph was 3–4 (3,70 ± 0,48) days, the second instar nymph was 3–4 (3,90 ± 0,32) days, the third instar nymph was 3–4 (3,70 ± 0,48) days, the fourth instar nymph was 3–4 (3,80 ± 0,42) days, and the fifth instar nymph was 3–4 (3,60 ± 0,52) days. Age of female was 13–17 (15,30 ± 1,34) days. It was longer than age of male which was 8–12 (10,10 ± 1,20) days. Female could produce 181–214 (197,60 ± 11,64) eggs during its life. The sex ratio was 1:1,98.